EDUKASI POLA KEJAHATAN SIBER UNTUK ANTISIPASI PENIPUAN PADA SISWA SMA SANTO THOMAS 4 BINJAI - Manutur Pandapotan Siregar; Abwabul Jinan; Windi Saputri Simamora; Siti Sarah Harahap (Jurnal Abdi Insani, 2026)
The use of digital devices such as mobile phones has become an integral part of everyday life in modern society. Increased intensity of online activities also creates opportunities for cybercrime, including the distribution of spam, malware, viruses, and fraudulent links that may lead to data theft and financial scams. Limited public awareness and understanding of digital security are among the factors contributing to the increasing number of cybercrime cases. The purpose of this activity is to improve students’ knowledge and awareness regarding various forms of cybercrime and how to identify suspicious links. In addition, this activity aims to encourage students to act as digital literacy agents within their families. The method used in this activity was an educational outreach program on cybercrime for students. The materials presented included an introduction to the types of cybercrime, techniques for verifying the validity of links, and an understanding of mobile phone security settings and application permission management. The activity was conducted through presentations and interactive discussions related to the identification of suspicious links. The results of the activity indicate an improvement in students’ understanding of cybercrime threats and strategies to prevent them. Students were able to identify the characteristics of suspicious links and understand the importance of carefully managing application access permissions. In addition, students demonstrated increased awareness and caution when receiving messages or links from unknown sources. The discussions conducted during the activity revealed that most students previously had limited understanding of potential cyber threats. After participating in the activity, students were able to explain basic preventive measures to avoid cybercrime. These findings indicate that educational activities have a positive impact on improving digital security literacy. In conclusion, digital security education for students is effective in increasing awareness and understanding of cybercrime. Students have the potential to serve as agents of digital literacy within their families to help prevent cybercrime incidents.